The MORAL PANIC AND POLITICS OF MORAL – THE ROLE OF AUTHORITIES AND MIDDLE-CLASS IN THE GROWTH OF ISLAMIC POPULISM IN WEST SUMATRA - Lestari, Yayuk (Jurnal Ranah Komunikasi, 2023)
This study delves into the nuanced intersection between morality and populism in West Sumatra, specifically examining the emergence of Islamic populism post-Reform. In contrast to prevailing studies that predominantly scrutinize economic inequality and immigration within populist discourse, this research delves into the lesser-explored realm of moral and religious dimensions. Through the analysis of three pivotal factors influencing moral and populist politics, the study underscores the influence of local culture in reinforcing Islamic populism, the social bonds tethered to the cultural and religious identity of the Minangkabau ethnic group, and the synchronization of governmental political strategies with societal religious and cultural ethos. This study using a qualitative approach. The data obtained by interviews, observations, and documentations. Findings illuminate the impact of social connections on individual behavior, societal norms, and institutional frameworks, particularly in guiding and shaping moral behavior. Conformity, entrenched in tradition and religion, holds substantial sway in societal evaluations and restraints. The communal societal perspective, prevailing over individualistic notions, serves as a regulatory force in tandem with community values